Effect of Leadership, Compensation and Work Environment on Performance, With Job Satisfaction As The Intervening Variable In Employees PT. Sembilan Cahaya Abadi - Anshori, Miftahul; Nurwulandari, Andini (Ridwan Institute, 2021)
The purpose of this study was to analyze the influence of leadership, compensation, and work environment on employee performance with job satisfaction as an intervening variable at PT. Sembilan Cahaya Abadi. The research sample was 125 people who were selected by random sampling method. Data collection using questionnaires and Structural Equation Modeling (SEM) was used as an analytical technique. The results of the study prove that the variables of Leadership, Compensation, and Work Environment have a positive and significant effect on Employee Performance through Job Satisfaction.